Consanguinity via Breastfeeding in view of Islam and Science of Epigenetics - Mahmood, Silvia (Jurnal Medis Islam Internasional, 2023)
Background : One of the unique features of the Qur´an and Sunna is that never contradict the Science. Quran is not considered as a scientific book, however, includes many extraordinary signs and true scientific facts that have not been known at the time of the Quran revelation. Over the past few decades, several of them have been revealed, but many are still waiting to be uncovered. Result : Breastfeeding is the most natural and safest way to provide nutrition, protection and unique bonding experience for newborn babies. The term “milk-kinship” is a kind of relationship via breastfeeding that was established hundreds of years ago via the Qur´an and Sunna. The study revealed that the life expectancy of the F2 offspring obtained from milk-sublings mating was much shorter than the offspring from control group. Which mean that there is period in which offspring are susceptible to breast milk induced epigenetic changes, especially in the first 2 years of life. Conclusion : Recent research suggests that consanguinity via breastfeeding can be explained by heritable mechanism of epigenetic modifications.